Incentive device improves spacer technique but not clinical outcome in preschool children with asthma - Schultz, A.; Sly, P.; Zhang, Guicheng; Venter, A.; Le Souãf, P.; Devadason, S. (2012)
Aim: To investigate the influence of an incentive device, the Funhaler, on spacer technique and symptom control in young children with asthma and recurrent wheeze. Methods: Randomised controlled trial where 132 2-6 year old asthmatic children received regular inhaled fluticasone through Aerochamber Plus, or Funhaler. The setting was a research clinic at Princess Margaret Hospital for Children, Perth, Australia. Subjects were followed up for a year. The main outcome measure was asthma symptoms. Proficiency in spacer technique was measured as salbutamol inhaled from spacer onto filter. Quality of life was measured every three months. Groups were compared in terms of spacer technique, symptoms and quality of life. The relationship between spacer technique and clinical outcome was examined. Results: There was no difference between Funhaler and Aerochamber groups in wheeze free days, cough free days, bronchodilator free days or quality of life (P = 0.90, 0.87, 0.74 and 0.11 respectively). Spacer technique was better in the Funhaler group (P = 0.05), particularly in subjects younger than 4 years of age (P = 0.002). Drug dose on filter (as the mean of five 100 mg doses) ranged from zero to 136 mg. Conclusions: Use of Funhaler incentive device does not improve clinical outcome, but improves spacer technique in children younger than 4 years. Variability in drug delivery is large in young children using pressurised metered dose inhalers and spacers. © 2011 Paediatrics and Child Health Division (Royal Australasian College of Physicians).